Rio Bravo - Hawks, Howard, 1896-1977.; Furthman, Jules; Brackett, Leigh; McCampbell, B. H.; Wayne, John, 1907-1979.; Martin, Dean, 1917-1995.; Nelson, Rick, 1940-1985.; Dickinson, Angie; Brennan, Walter, 1894-1974.; Bond, Ward, 1903-1960.; Russell, Johnnie, 1921-; Rodriguez, Estelita, 1928-1966.; et al. (Burbank, CA : Warner Home Video, 2001)
A Texas border sheriff fights off hired gunmen to keep a murderer in custody.
DVD.
English soundtrack (Dolby mono) with optional English, French, Spanish or Portuguese subtitles ; close-captioned for the hearing impaired.
John Wayne, Dean Martin, Ricky Nelson, Angie Dickinson, Walter Brennan, Ward Bond, John Russell, Pedro Gonzalez-Gonzalez, Estelita Rodriguez, Claude Akins, Malcolm Atterbury, Harry Carey, Jr.
Director of photography, Russell Harlan ; editor, Folmar Blangsted ; music, Dimitri Tiomkin ; lyrics, Paul Francis Webster.
Widescreen format.
Originally released as a motion picture in 1958.
Keywords: Sheriffs -- Texas -- Drama; McCampbell, B. H. -- Film and video adaptations; Western films; Feature films; Video recordings for the hearing impaired; Cidades pequenas; Criminosos; Alcoâolatras.; Estados Unidos -- Oeste